Kepercayaan Orangtua Kepada Lembaga Pendidikan Islam - Muslikhatun, Muslikhatun; , Dr. Moordiningsih, M.Si, Psi (2016)
The education system in Indonesia found more of the country educational institutions, private and private educational institutions. As well as Islamic educational institutions have been in demand by today's society, even though many Islamic education in the interest of the community but the threat is always there progress of education quality that many other educational institutions are more resilient and qualified. The study have understood and described the process of the formation of the psychological dynamics of trust parents to Islamic educational institutions. Informants in this study came from a housewife who has a son or daughter who is studying or has graduated from UMS about 10 people. This study uses a qualitative method using interview techniques every informant. The study have found that based on interviews with ten informants who came from families who has Muslims and non-Muslims obtained that Islamic schools, the good or great in the eyes of society, good facilities, the cost of standard or not too expensive, many students who comes from outside the island of Java, and the oldest Islamic University in the city of Solo. The institute is open to all people and all religions in Indonesia. The agency also did not distinguish between the teaching systems for your son or daughter informant studying subjects except religion. The students from non-Islamic religious subjects did not burdened with the Islamic religion.